Sistem Notifikasi Surat Pada Kantor Pemerintahan Kota Langsa Berbasis Web - Harys Fajri HF; Eka Julianti; Ahmad Ihsan (Jurnal Informatika dan Teknologi Komputer (J-ICOM), 2021)
Notifications are notifications about actions that affect them. This notification can help users be more aware of events related to them and, if they want, can take action quickly, this notification is indispensable for letters, Letters can be interpreted as a means of communication to convey written information by one party to another by purpose tells the intent of the message from the sender. This notification system is made using PHP which will be designed using ERD and DFD and will produce a web with notification system for incoming and outgoing mail.